2016
DOI: 10.1093/brain/aww189
|View full text |Cite
|
Sign up to set email alerts
|

Auto-antibodies to contactin-associated protein 1 (Caspr) in two patients with painful inflammatory neuropathy

Abstract: Auto-antibodies against the paranodal proteins neurofascin-155 and contactin-1 have recently been described in patients with chronic inflammatory demyelinating polyradiculoneuropathy and are associated with a distinct clinical phenotype and response to treatment. Contactin-associated protein 1 (Caspr, encoded by CNTNAP1) is a paranodal protein that is attached to neurofascin-155 and contactin-1 (CNTN1) but has not yet been identified as a sole antigen in patients with inflammatory neuropathies. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
187
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(201 citation statements)
references
References 33 publications
10
187
2
2
Order By: Relevance
“…Our data show efficacy of rituximab in patients with an associated haematological disease (group 1), as reported by Benedetti and et al, and also in a second group of patients with autoimmune diseases. In a similar way, patients with anti‐neurofascin 155 antibodies have been reported to derive benefit from rituximab …”
Section: Discussionmentioning
confidence: 84%
“…Our data show efficacy of rituximab in patients with an associated haematological disease (group 1), as reported by Benedetti and et al, and also in a second group of patients with autoimmune diseases. In a similar way, patients with anti‐neurofascin 155 antibodies have been reported to derive benefit from rituximab …”
Section: Discussionmentioning
confidence: 84%
“…This observation was confirmed in 7% of 533 Japanese patients with CIDP showing ataxia, tremor, poor response to intravenous Ig and, in 3 patients, central nervous system demyelination 52. Finally, antibodies directed exclusively to Caspr1 were described in one patient with CIDP with prominent neuropathic pain 5. Overall, the patients harbouring antibodies against proteins of paranodal junctions account for about 10% of all patients classified as CIDP.…”
Section: Chronic Autoimmune Paranodopathies: Expanding the Conceptmentioning
confidence: 77%
“…At last, the description of a patient with the clinical picture of GBS and severe neuropathic pain, RCF and IgG3 anti-Caspr1 antibodies activating complement suggested that reactivity to paranodal Caspr1, with a mechanism similar to antiganglioside antibodies, could be also involved in acute autoimmune neuropathies 5. The dichotomous classification of neuropathies into axonal or demyelinating might be inadequate in the diagnosis of GBS subtypes.…”
Section: Acute Autoimmune Nodopathies: the Proposal Of The Conceptmentioning
confidence: 99%
“…Of some nerve biopsies, one part was used for the preparations of teased nerve fibres by gently teasing the fibres prefixed with paraformaldehyde 4% on a slide. Immunofluorescence double-staining with antibodies against myelin basic protein (GeneTex, 1:200) and Caspr (Abcam, 1:100), pan-neurofascin (Abcam, 1:400) and pan-sodium-channel (Sigma Aldrich, 1:100) was then performed as previously described 6. Skin biopsy sections were stained with the same combinations of antibodies for longitudinal assessment of dermal myelinated fibres according to protocols of a former study 14…”
Section: Methodsmentioning
confidence: 99%